Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which equation represents a line that passes through the points [tex]\((3, 1)\)[/tex] and [tex]\((6, 6)\)[/tex], we need to follow these steps:
1. Calculate the slope [tex]\( m \)[/tex] of the line:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Given the points [tex]\((3, 1)\)[/tex] and [tex]\((6, 6)\)[/tex],
[tex]\[ m = \frac{6 - 1}{6 - 3} = \frac{5}{3} \][/tex]
2. Formulate the point-slope form of the equation:
The point-slope form of a line's equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Using the point [tex]\((3, 1)\)[/tex] and the calculated slope [tex]\( \frac{5}{3} \)[/tex],
[tex]\[ y - 1 = \frac{5}{3}(x - 3) \][/tex]
3. Compare with the given options:
We are given the options:
- A. [tex]\( y + 6 = \frac{3}{5}(x + 6) \)[/tex]
- B. [tex]\( y - 1 = \frac{5}{3}(x - 3) \)[/tex]
- C. [tex]\( y - 6 = \frac{3}{5}(x - 6) \)[/tex]
- D. [tex]\( y + 1 = \frac{5}{5}(x + 3) \)[/tex]
Clearly, option B matches our equation derived from the steps above.
Therefore, the correct equation that represents the line passing through the points (3, 1) and (6, 6) is:
B. [tex]\( y - 1 = \frac{5}{3}(x - 3) \)[/tex]
1. Calculate the slope [tex]\( m \)[/tex] of the line:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Given the points [tex]\((3, 1)\)[/tex] and [tex]\((6, 6)\)[/tex],
[tex]\[ m = \frac{6 - 1}{6 - 3} = \frac{5}{3} \][/tex]
2. Formulate the point-slope form of the equation:
The point-slope form of a line's equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Using the point [tex]\((3, 1)\)[/tex] and the calculated slope [tex]\( \frac{5}{3} \)[/tex],
[tex]\[ y - 1 = \frac{5}{3}(x - 3) \][/tex]
3. Compare with the given options:
We are given the options:
- A. [tex]\( y + 6 = \frac{3}{5}(x + 6) \)[/tex]
- B. [tex]\( y - 1 = \frac{5}{3}(x - 3) \)[/tex]
- C. [tex]\( y - 6 = \frac{3}{5}(x - 6) \)[/tex]
- D. [tex]\( y + 1 = \frac{5}{5}(x + 3) \)[/tex]
Clearly, option B matches our equation derived from the steps above.
Therefore, the correct equation that represents the line passing through the points (3, 1) and (6, 6) is:
B. [tex]\( y - 1 = \frac{5}{3}(x - 3) \)[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.